Parents’ social comparisons and adolescent self-esteem: the mediating effect of upward social comparison and the moderating influence of optimism - Liu, Hongyang; Kvintova, Jana; Vachova, Lucie (Frontiers in Psychology, 2025)
Parents’ social comparison is a common phenomenon that occurs in China. It refers to the behavior of parents imagining other people’s children as an excellent role model without shortcomings and comparing their own children with them. This behavior may affect their child’s mood. The purpose of this study was to explore the impact of parents’ social comparison on adolescents’ self-esteem through the mediating role of upward social comparison, and to explore the moderating role of optimism in upward social comparison and self-esteem. Parents’ social comparison questionnaire, upward social comparison questionnaire, self-esteem questionnaire and life orientation questionnaire were distributed through online questionnaires, and 576 valid questionnaires were received. The results of the study found that upward social comparison plays a partial mediating role in the negative impact of parents’ social comparison on self-esteem, and optimism plays a moderating role in the impact of upward social comparison on self-esteem. This study illustrates the harmful effects of parents’ social comparison on adolescent mental health, but this harm can be mitigated through the teaching of optimism. This study shows that parents’ social comparison is not advisable, and attention should be paid to maintaining the optimistic attitude of teenagers to ensure their healthy growth.